An Unexpected Cause of De Novo Urge Incontinence Following Artificial Urinary Sphincter Placement: A Case Report - Ante Jakšić; Iva Žuža; Ivan Marin Sušanj; Ivan Vukelić; Josip Španjol; Dean Markić; Argimiro Collado Serra; Antun Gršković (Journal of Clinical Medicine, 2026)
Background: Stress urinary incontinence is one of the most common and debilitating complications following radical prostatectomy. Artificial urinary sphincter (AUS) implantation is the gold standard treatment for moderate to severe post-prostatectomy incontinence. Common complications include device infection, mechanical failure, component migration, urethral erosion, and urethral atrophy, which often require device removal and subsequent reimplantation. To our knowledge, erosion or migration of orthopedic osteosynthesis screws into the lower urinary tract causing new-onset urinary symptoms after AUS implantation has not previously been reported. Case Presentation: A 57-year-old man with an implanted AUS presented to the emergency department with fever, dysuria, and de novo urge incontinence. Intravenous antibiotic therapy was initiated, resulting in resolution of the fever, after which further diagnostic evaluation was performed. Cystoscopy demonstrated normal urethral coaptation and intact urethral mucosa at the cuff site. However, three orthopedic osteosynthesis screws from previous pelvic fracture fixation were identified protruding immediately below the bladder neck. The screws were removed by open surgery during ongoing empirical antimicrobial therapy. Four weeks later, the AUS was reactivated. At 8-month follow-up, the patient remained asymptomatic and maintained the same continence status as following AUS implantation. Conclusions: A detailed history of previous pelvic surgery and orthopedic fixation, together with review of available imaging, is important in candidates for AUS implantation. In patients presenting with new-onset urinary symptoms after AUS implantation, alternative etiologies should be considered, with cross-sectional imaging and cystoscopy used selectively according to the clinical presentation.